PARTISIPASI POLITIK MASYARAKAT DALAMPEMILIHAN UMUM WALIKOTA/WAKIL WALIKOTA PALANGKA RAYA TAHUN 2013 DI KECAMATAN PAHANDUT (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2014)
This study aims to describe how people's political participation in elections Mayor / Deputy Mayor of Palangkaraya in District Pahandut in 2013. People's political participation can be seen through the participation of the community in the campaign and polling (voting) can finally be concluded that the level of political participation of the community.Data sources of this study is secondary data which have been obtained from the District Election Committee (PPK) and Pahandut of the Voting Committee (PPS) in every village in the district Pahandut. Data collection techniques by performing the study and documentation of the village other materials related to the study. Field research is the data collection by jumping to a location using the enclosed questionnaire (questionnaire) as well as an interview with the head of the KDP Pahandut and communities have the right to vote.Sampling using Taro Yamane formula. Samples were taken of the number of voters registered in the voters list (DPT) in District Pahandut as many as 100 people from 49 160 people. While the data analysis technique used is descriptive quantitative in order to give an idea of the level of political participation in elections Mayor / Deputy Mayor Palangkaraya Pahandut Year 2013 in the district, whether it is through one's participation in the campaign and voting (voting).The results showed that the level of political participation of the community in the form of participation in campaign activities is still low at only 46 %. While the level of political participation of the community in the form of participation in the provision of voting rights (the election) is relatively high at 74.50 %.